1989
DOI: 10.1177/073346488900800109
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Loneliness Among the Elderly

Abstract: Based on a deprivation model of religiosity we analyze the relationship between two dimensions of religiosity and loneliness among the elderly with the effects of involvement in various types of family and friendship relations controlled and compared with the effects of religiosity. Data were collected through interviews with 131 residents of a 199-unit apartment facility for the elderly. Results of the regression analysis showed that greater involvement in the social aspects of religion was significantly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 19 publications
2
22
1
Order By: Relevance
“…However, we believe that the literature supports religion's positive influence in these areas and agree with Johnson and Mullins (1989) who note in their summary of research on religion in later life and on well-being that &dquo;the weight of evidence suggests that religious faith or involvement contributes to a sense of well-being&dquo; (p. 111). Regarding coping, Koenig, George, and Seigler (1988) say that &dquo;regardless of geographic location, race, sex, and socioeconomic status, religious coping behaviors are common among older adults&dquo; (p. 308).…”
Section: Implications For Practitioners/service Providerssupporting
confidence: 61%
See 1 more Smart Citation
“…However, we believe that the literature supports religion's positive influence in these areas and agree with Johnson and Mullins (1989) who note in their summary of research on religion in later life and on well-being that &dquo;the weight of evidence suggests that religious faith or involvement contributes to a sense of well-being&dquo; (p. 111). Regarding coping, Koenig, George, and Seigler (1988) say that &dquo;regardless of geographic location, race, sex, and socioeconomic status, religious coping behaviors are common among older adults&dquo; (p. 308).…”
Section: Implications For Practitioners/service Providerssupporting
confidence: 61%
“…The nature of religious behavior in later life is indeed complex. The importance of viewing religiosity in old age in a multidimensional manner and the limitations of conceptualizing religious behavior solely in terms of church-related activities have been noted (Johnson & Mullins, 1989;Mindel & Vaughan, 1978). Mindel and Vaughan admit that had only organizational religious criteria, primarily church attendance, been used in their study of religiosity in old age, over half of their elderly sample would have been designated as nonreligious or withdrawn from religion (p. 108).…”
mentioning
confidence: 97%
“…Different studies have reported positive correlations between church or synagogue attendance and general well-being (Mull, Cox and Sullivan 1987;Steinitz 1980) and life satisfaction (Guy 1982;Levin and Markides 1988;Markides 1983), between religious activities and morale (Koenig, Kvale and Ferrel 1988), selfesteem (Krause and van Tran 1989), lower levels of loneliness (Johnson and Mullins 1989), and personal adjustment (Moberg 1956;Blazer and Palmore 1976), between intrinsic religiosity and life satisfaction (Haitsma 1986) and self-esteem (Nelson 1990), between religious commitment and life satisfaction (Rogalski and Paisey 1987), between religious coping mechanisms and lower levels of depression (Koenig, Cohen, Blazer, Pieper, Meador, Shelp, Goli and DiPasquale 1992) and between religious orthodoxy and happiness (Hunsberger 1985).…”
Section: Introductionmentioning
confidence: 98%
“…However, the groups differed in some correlates of loneliness and in ways of experiencing it. Recently Johnson and Mullins (1989) studied the relation between religiosity and loneliness among generally healthy elderly persons. The more involved people were in the social aspects of religion (church or synagogue attendance and visiting with friends from the respondent's religious group), the less lonely they were.…”
mentioning
confidence: 99%